SOBRE LAS GRAMÁTICAS BILINGÜES Y LA PERMEABILIDAD ESTRUCTURAL - Landa, Alazne; Elordui, Agurtzane (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Drawing from data on several language contact situations, this paper aims to provide some empirical evidence in support of the hypotheses that (i) at the morphosyntactic level, influence from another language is hard to demonstrate and, if it exists, it can only exist indirectly;, (ii) external influence consists at most of the exploitation of a previous surface-level structural similarity between the languages involved in the contact situation (Prince 1992); and (iii) hypotheses (i) and (ii) also apply to terminal dialects; however, these dying varieties undergo different types of simplification processes that can be best accounted for in terms of a combination of language-internal, cognitive and interactional factors. The tendency towards grammar simplification is claimed to be rather universal, although accelerated in the case of dialect death (Dorian 1981), and a number of allegedly contact-induced phenomena are reinterpreted as instances of relaxation of different types of constraints in bilingual grammars. The data on which this research is based have been collected from the following language contact situations: (a) Basque-Spanish in the Basque Country (Elordui 1995, Landa 1995), (b) Spanish-English in the United States (Landa 1992, Silva-Corvalán 1994), and (c) Basque-English in Nevada, U.S.A. (Elordui 1998c).